2020
DOI: 10.3390/pathogens9110888
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Features and Evolution of the Parapoxvirus during the Past Two Decades

Abstract: Parapoxvirus (PPV) has been identified in some mammals and poses a great threat to both the livestock production and public health. However, the prevalence and evolution of this virus are still not fully understood. Here, we performed an in silico analysis to investigate the genomic features and evolution of PPVs. We noticed that although there were significant differences of GC contents between orf virus (ORFV) and other three species of PPVs, all PPVs showed almost identical nucleotide bias, that is GC richn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
1
6
0
2
Order By: Relevance
“…Sequences from 2021 to 2022 indicated that the virus had barely mutated. This suggests a common source of infection and is no surprise as the evolutionary rate of large DNA viruses is slow [35] and previous studies have reported mutation rates of 10 −6 –10 −4 substitutions/site/year for poxviruses [36, 37]. Even though analysing the viral sequences can be used to track outbreaks and estimate transmission routes of many viruses, partial Sanger sequencing of the circulating EqPPV variants could not be applied for this outbreak due to nonexisting variation.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences from 2021 to 2022 indicated that the virus had barely mutated. This suggests a common source of infection and is no surprise as the evolutionary rate of large DNA viruses is slow [35] and previous studies have reported mutation rates of 10 −6 –10 −4 substitutions/site/year for poxviruses [36, 37]. Even though analysing the viral sequences can be used to track outbreaks and estimate transmission routes of many viruses, partial Sanger sequencing of the circulating EqPPV variants could not be applied for this outbreak due to nonexisting variation.…”
Section: Discussionmentioning
confidence: 99%
“…Virokine sind virale Homologe ihrer oft antiinflammatorischen Pendants im Wirt, zum Beispiel virales IL-10 von Parapoxviren. 22 Natürliche Killerzellen, CD4 + und CD8 + Lymphozyten spielen als Teil des adaptiven Immunsystems eine Schlüsselrolle bei der Virusbeseitigung zur Kontrolle der Primärinfektion. 23,24 Pockenvirusinfektionen können die Lebensqualität stark beeinträchtigen, insbesondere bei komplizierten Erkrankungsverläufen mit Beteiligung des zentralen Nervensystems (ZNS), der Atemwege oder des Binde-und Stützgewebes, die auf peri-/postinfektiöse Prozesse, aber auch auf die direkte Virusinfektion zurückzuführen sind.…”
Section: Genus Speziesunclassified
“…viral IL-10 of parapoxviruses which can suppress immune response. 22 Natural killer cells, CD4 + and CD8 + lymphocytes, as part of the adaptive immune system, play a key role in viral clearance to control primary infection. 23,24 Only limited data is available on the risk of reinfection with a certain poxvirus species or strain, leading to symptomatic disease again.…”
Section: Associated Human Diseasementioning
confidence: 99%